Comparison of Fitness of Casted Cr-Co with Selective Laser Sintering (SLS) Technology of Cr-Co and CAD/CAM Milled Acetal Major Connector Materials - Bashar Mohammed Al Noorachi / Ali Jameel Al Sudany ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Newly developed materials and manufacturing processes offer different treatment modalities, such new treatment options need investigation and comparison to achieve long lasting, hygienic and health preserving prosthesis. This study was aimed to compare the fitness of three different materials Casted Cobalt Chromium, Selective Laser Melting Cobalt Chromium and Milled Polyoxymethylene (POM) Acetal. SLS Co-Cr shows superior fitness qualities that Acetal and Casted Co-Cr respectively